Analisis Ekspor Kopi Indonesia pada Pasar Internasional - Riska Dwi Maulani; Diah Wahyuningsih (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2021)
This study aims to analyze the effect of Gross Domestic Product (GDP), exchange rates, international coffee prices and coffee production on the value of Indonesian coffee exports in the six countries (United States, Germany, Japan, Italy, Malaysia, and the United Kingdom). The data used in this study are secondary data in the form of panel data analysis method is a combination of time series and cross section for the period 2009-2018. Data processing is done using Stata 14. The results of this study indicate that the real GDP variable has a positive and significant effect on the value of Indonesia's coffee exports in six destination countries. The exchange rate does not significant effect on the value of Indonesian coffee exports in six destination countries international coffee prices have a positive and significant effect on the value of Indonesian coffee exports in six destination countries. Domestic production has a positive and significant effect on the value of Indonesian coffee exports in six countries the value of the dete coefficient rminasi (R2) is obtained at 0.9474. This means that of the four independent variables namely real GDP, exchange rates, international coffee prices, and production are able to explain the dependent variable namely the value of Indonesian coffee exports of 94.74% and the remaining 5.26% explained by other variables.